The Relationship Of Menarche Age And Body Mass Index (BMI) In Adolescent Girls At SMP Negeri 6 Denpasar - Ni Luh Ayu Sangging Giri Antari; Niken Ayu Merna Eka Sari; I Gusti Ayu Putu Satya Laksmi (Rena Cipta Mandiri, 2026)
Young women are a group of 10–19 years old who experience a transition period to adulthood, characterized by the occurrence of menarche. The age of menarche needs to be considered because too early menarche can have an impact on the reproductive health and nutritional status of adolescent girls. Changes in adolescent lifestyles that trigger an increase in Body Mass Index (BMI) are suspected to play a role in accelerating the age of menarche. The purpose of this study was to determine the relationship between menarche age and BMI in adolescent girls at SMP Negeri 6 Denpasar. The study used a quantitative method with a cross sectional observational analytical design. The sampling technique used was convenience sampling with 237 respondents who were selected according to the inclusion and exclusion criteria. The results showed that most of the respondents experienced the normal menarche age category (11-13 years) as many as 217 people (91.6%), the majority of respondents had a normal BMI, which was 186 people (78.5%). The Spearman's Rho test showed that there was a significant relationship between the age of menarche and body mass index (BMI) with values of r = -0.178 and p = 0.006 (p < 0.01). This relationship is negative and weak, meaning that the higher the BMI, the menarche age tends to occur faster, and conversely, the lower the body mass index, the later the menarche age tends to occur. These results indicate that nutritional status plays a role in determining the time of menarche. This is in line with the theory that increased body fat can affect the hormone leptin which accelerates puberty. Thus, although the relationship found to be weak, the results of this study confirm that nutritional status, especially BMI, is one of the factors that need to be considered in the reproductive development of adolescent girls.